Analysis of Instrument Development to Evaluate Employee Protection from Tuberculosis in Hospitals - Lestari, Fetrina; Modjo, Robiana; Kurniawidjaja, Meily; Susanto, Agus Dwi; Alfiyyah, Arifah (The Indonesian Journal of Occupational Safety and Health, 2024)
Introduction: Tuberculosis (TB) continues to be a major global public health threat, affecting millions of people annually. Despite efforts to control TB, the number of cases remains high. The situation is exacerbated by the COVID-19 pandemic, which has strained healthcare systems. The increased workload of hospital employees also raises the risk of TB transmission. This study aims to develop an instrument to evaluate employee protection from TB in hospitals. Methods: This study used a qualitative design with an exploratory approach. Data were collected from existing policies and through in-depth interviews with stakeholders, including academics, practitioners, regulators, infection control officers, occupational health and safety officers, and non-government organization representatives for TB. Results: The instrument developed comprised seven components, namely management commitment; program planning; coordination, communication, and education; implementation of TB and other disease management programs in the workplace; handling TB cases in the workforce; training and competence; and monitoring and evaluation. Conclusion: Instrument development is crucial for capturing the current state of TB problems and managing prevention and control programs in hospitals. The terms of reference serve as an effort to protect hospital employees